New Perspectives on affect and learning technologies - Calvo, Rafael A.; D?Mello, Sidney (Explorations in the learning sciences, instructional systems and performance technologies, 2011)
Of all the differences between human beings and computers, emotion is perhaps the most basic: humans have them and use them; machines do not, except with human help. One of the most promising arenas for human/computer intervention has been in the form of educational technologies that respond to the intersection of affect and cognition that occurs during learning. Synthesizing knowledge across psychology, education, computer science, and related fields, these affect-sensitive learning environments coordinate pedagogy with student emotions to promote optimal learning. The first full-length treatment of its subject, New Perspectives on Affect and Learning Technologies explores new theoretical perspectives and technological advances concerning the role of affect in learning. Broadening this concept to include related constructs of motivation, engagement, metacognition, and creativity, the book mines a wealth of behavioral, physiological, and linguistic data for a state-of-the-art survey of affective computing in education. This interdisciplinary approach, in turn, adds to the knowledge base on the affective components of students? learning experience. Chapter authors provide dispatches from all corners of the field, including: Current neuroscientific findings on emotion and learning. Pedagogical and motivational strategies sensitive to affective and cognitive processes. Multimodal human/computer interfaces, with emphasis on affect recognition. Innovations in methodologies for investigating affect and learning. Design issues in developing affect-aware learning environments. Latest advances in intelligent tutoring systems. New Perspectives on Affect and Learning Technologies deserves a wide audience among researchers in learning technologies, affective computing, human/computer interaction, artificial intelligence in education, and intelligent tutoring systems, as well as the greater educational research and cognitive science communities.